Pengaruh Pelatihan Pasar Modal, Persepsi Mahasiswa, Modal Minimal dan Hubungan Pertemanan pada Minat Berinvestasi - Putra, Ida Bagus Putu Pramana; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
The purpose of this study was to determine the effect of Capital Market Training, Student Perception, Minimum Capital and Friendship Relationships on Interest in Investing. This research was conducted at the Faculty of Economics and Business, University of Udayana Economics for Accounting S1 students. This study uses multiple linear regression analysis techniques. In determining the sample of this study using Slovin formula for known populations. The sample amounted to at least 75 respondents who were active students of the 2015 class and had taken capital market theory courses. Data used in this study is quantitative, in the form of the results of answers by respondents stated in the form of numbers from questionnaires measured using a Likert scale. The results of the analysis show that, minimum capital has a negative effect on investment interest and capital market training, student perceptions, friendship relations have a positive effect on investment interest. Keywords : Capital market training, student perceptions, minimal capital, friendship, interest in investing